What Kind of Learning Community Do Teachers Constitute? - Anna Borukało; Andrzej Kiciński (University of Lower Silesia, 2013)
For twenty years, Polish schools have been going through permanent reforms. The changes have been triggered by the need for systematic changes, requirements of the European integration, modernization, and the demands of the market and the economy. On the one hand, such actions motivate educational institutions to engage in ongoing innovations and improvement of qualifications, but on the other hand they may and as a matter of fact they do result in the state of overload, insecurity and dissent among teachers. In this article, as practicing teachers, we will focus on selected themes arising from the predicament of teachers who face continuous changes. In the first part of the article, we are elaborating on some aspects and problems we have come across in our school practice with which teachers across different school types and levels are familiar. In the second part, we are presenting our findings and reflections related to being members of the teaching staff; we are trying to show the structure of the teachers' team, its diversity and possibilities for professional growth.